FAKTOR-FAKTOR PENYEBAB KEMACETAN DI DKI JAKARTA - Rohana Sitanggang; Euis Saribanon (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
Finding a solution in overcoming the bottleneck problems, we need to focus on the factors that affect the bottleneck . DKI Jakarta as the capital city has a very busy activity intensity, because it is the center of activity not only from indigenous people but also from residents around the region such as from Bekasi, Tanggerang, Depok and Bogor. Hence, it needs to subscribe an integrated transportation system with all related area. The purpose of this research is to find the causal factor of congestion that happened in DKI Jakarta in order to determine the most relevant transportation system policy applied in DKI Jakarta. By purposive sampling and quoted sampling method, there were 30 respondents from road users and communities around Jalan Cawang - Grogol and Kota Tua - Harmony. In processing questionnaire data, SPSS program version 19 was used with Descriptives analysis method. The result of this research is there are 3 order of the top ranking factors which cause traffic jam in DKI Jakarta that is 1). The use of Personal Vehicle in Jakarta is very high, 2). The use of two-wheel motorcycles in Jakarta is very high and 3). Vehicle volume is not proportional to road capacity.